Inflammatory myofibroblastic tumor of the bladder: case report and review of the literature - Wei, Li; Jianbo, Liang; Qiang, Wei; Hai, Yu; Zhixiang, Lan (Canadian Urological Association Journal, 2013)
Inflammatory myofibroblastic tumor (IMT) is a rare tumor with malignant potential, and it has been described in many major organs. However, bladder location is very uncommon. We report the case of a 23-year-old women presented with painless gross hematuria last for 2 weeks. Contrast-enhanced computed tomography (CT) revealed a bladder tumor. The patient underwent a open partial cystectomy and the final pathologic diagnosis was inflammatory myofibroblastic tumor of bladder. Typical IMTs can be locally aggressive, thus close follow-up is necessary.